The Impact of Financial Development on Bank Investment in Iraq - Ghanem Yahya *, Yasser; Saleh Salman , Mohammed (Journal of Economics and Administrative Sciences, 2024)
Theoretically, the literature indicates that financial development has a positive effect on investment. therefore this study aim to determine the impact of the financial development on investment banking in iraq, during the semi-annual period (2005-2021) using autoregressive distributed lag (ardl), and using the toda yamamoto causal test, the result of the bound test (ardl) showed a long-term cointegration relationship between variables , the model showed that the financial depth positively affect the investment banks against the negative effect of the long-term financial stability index, while toda yamamoto causal test showed that there is no causal relationship between financial development and investment banking.